Effects of Contrast Training with Two Sessions Weekly Frequency on Physical Fitness of University-Level Male Soccer Players - Rohit Kumar Thapa; Gopal Kumar; Shiny Raizada; Amritashish Bagchi (OVS LLC, 2023)
The purpose of this study was to compare the effects of a six-week contrast training intervention conducted twice per week during the preparatory period on the measures of physical fitness in university-level male soccer players. Materials and methods. Sixteen players were selected as participants and randomly assigned to an experimental group or an active control group. Data were collected at baseline and after a six-week training intervention period for 15 m and 30 m linear sprint, medicine ball throw (MBT), standing long jump (SLJ), countermovement jump (CMJ), change of direction speed (CODS), peak torque (both legs) during extension and flexion, and running-based anaerobic sprint test (RAST). Results. The analysis revealed reported significant small to very-large magnitude within-group improvement in all the dependent variables for the experimental group (p<0.001-0.028) but not for the control group (p=0.066-1.000). Further, the analysis of covariance with the pre-test scores as covariates revealed significant differences at post-intervention assessments for all the dependent variables, favoring the contrast training group (p<0.001-0.05). Conclusions. A six-week contrast training intervention with two weekly sessions during the preparatory period may be sufficient to induce small improvement in the 30 m linear sprint and isokinetic strength of both legs, moderate improvement in the 15 m linear sprint, and MBT, large improvements in SLJ, RAST, and a very large improvement in vertical jump (CMJ) and CODS.